Use of prehospital dressings in soft tissue trauma: is there any conformity or plan?. Issue 7 (22nd June 2009) - Jones, A P; Allison, K; Wright, H; Porter, K
Abstract : Background: Acute soft tissue wounds are commonly seen in the prehospital setting. It was hypothesised that there is a lack of consistency in early management of trauma wounds, particularly in the dressings used. Methods: In January 2007 a questionnaire-based study was undertaken to evaluate the early management of such injuries. All 13 UK ambulance services were contacted, as well as 2 voluntary ambulance services. The questionnaire considered the implementation of a wound treatment policy and staff training, immediate wound management including haemostasis, cleansing, analgesia, dressings and the use of antibiotics. Results: The response rate was 100%. Only 27% of services had a wound treatment policy in place, but all services implemented staff training. All services regularly achieved haemostasis of wounds using a combination of pressure and elevation. Regular cleansing was performed by 47% of services and those that did so used normal saline or water. All ambulance services administered analgesics. The most commonly used analgesics were Entonox and intravenous morphine. Other analgesics administered were paracetamol and ibuprofen. No local anaesthesia was used. Dressings were applied regularly by all services; 13 different types of dressings were in regular use. Conclusions: This study confirmed that there is currently no national standard protocol for early acute wound management in the prehospital care setting. The key areas for improvement are cleansing, simplification of dressings and the introduction of standardised protocols and teaching.